MANAGEMENT OF DYSTOCIA DUE TO CONJOINED TWINS IN GRADED MURRAH BUFFALOES: A REPORT OF TWO CASES - RUHIL, SWATI; POTLIYA, SANDEEP; SINGH, HARPREET; KUMAR, ANKIT; BISLA, RANBIR SINGH (The Indian Journal of Animal Reproduction, 2023)
In the present study, the two uncommon cases of foetal anomalies in buffaloes; one with complete duplicationand other with only anterior duplication were reported.
Keywords: Dystocia; Conjoined twins; caesarean section; buffaloes